SOCIAL TYPES CHARACTERISTIC OF THE CHACO TERRITORIANO (1884-1950). THEIR CONDITIONS OF LIFE, AND INFLUENCE ON THE IDENTITY OF THIS SPACE. - Mari, Oscar Ernesto (Revista de Historia Social y de las Mentalidades, 2024)
The occupation of the Southern Chaco Argentine between ends of the nineteenth century and early decades of the 20th, was boosted by successive phases colonizers that they accompanied differentiated economics cycles. In each one of these moments, that were given in different geographic areas within the Territory, went forming social groups individuals that contributed the first identity traits to this society in training. Within these, emerged social types that motivated first images with that the domestic society identified to Chaco. Living conditions and work, and it contributes the cultural of some sectors representing the rural field of Chaco in this period, are issues addressed in the current article.